2023
DOI: 10.1186/s12871-023-02097-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for postoperative sleep disturbance in adults: a prospective survey of 640 patients undergoing spinal surgery

Abstract: Background Postoperative sleep disturbance (PSD) is a prevalent clinical complication that may arise due to various factors. The purpose of this investigation is to identify the risk factors for PSD in spinal surgery and establish a risk prediction nomogram. Methods The clinical records of individuals who underwent spinal surgery from January 2020 to January 2021 were gathered prospectively. The least absolute shrinkage and selection operator (LASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that preoperative anxiety and depression adversely affect sleep quality both before and after surgery. Higher levels of psychological distress correlate with poorer sleep quality during the perioperative period, leading to a higher incidence of PSD (Du et al, 2023;Gu et al, 2023;Huang et al, 2021;Mansano-Schlosser et al, 2017;S. J.Wang et al, 2022;Z.Wang et al, 2023;Wright et al, 2010).…”
Section: Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that preoperative anxiety and depression adversely affect sleep quality both before and after surgery. Higher levels of psychological distress correlate with poorer sleep quality during the perioperative period, leading to a higher incidence of PSD (Du et al, 2023;Gu et al, 2023;Huang et al, 2021;Mansano-Schlosser et al, 2017;S. J.Wang et al, 2022;Z.Wang et al, 2023;Wright et al, 2010).…”
Section: Antecedentsmentioning
confidence: 99%
“…Postoperative pain has been consistently identified as a risk factor for postoperative SD in surgical patients (Long et al, 2019;Miller et al, 2015;Özkan et al, 2023). Moreover, the type of surgery, high intraoperative bleeding, and postoperative passive positioning also elevate the risk of postoperative SD (Du et al, 2023;H. F.Zhang et al, 2018).…”
Section: Antecedentsmentioning
confidence: 99%
“…Postoperative sleep disturbance (PSD) can occur after surgery for various reasons, such as pain from the surgical incision site on the back and dysfunction of the autonomic nervous system. The incidence of PSD can be as high as 40% to 60% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Therefore, it is clinically significant to conduct early cognitive risk prediction, focusing on older adult patients with preoperative sleep disorders. Studies have explored the risk factors for perioperative sleep disorders, 10,11 while other studies have also explored the risk factors affecting postoperative cognitive outcomes. 2,12,13 However, no study has explored the specific risk factors for DNR in patients with preoperative sleep disorders.…”
mentioning
confidence: 99%